Experimental study for PV grid connected - Nur Yasmin, Amran (2012)
Photovoltaic grid connected system is the development trend of photovoltaicsystems. Nowadays, grid connected photovoltaic (PV) generation system is expectedmore widespread use due to fossil fuel cost. The measured data is used to investigatethe effects of PV grid connected system. Result from experimental and research bothis compared. To assess the impact on waveform and Total Harmonic Distortion(THD), Single phase motor is used as the load. The measurement technology elementof this project pertains to how power quality is being measured in this networkenvironment. Parameter such as input harmonics, input current waveforms, input voltage waveform, voltage (among others) at the input of the network is collected and analyzed.For obtaining high power, numerous PV cells are connected in series and parallel circuits on a panel, which is a PV module. A PV array is defined as agroup of several modules electrically connected in series-parallel combinations to generate the required current and voltage. From the experiments, it represents the performance of PV-grid connected system such as the voltage and current in this system. The scale down less than 1kW PV had been connected to 415V distribution feeder. The result consists of 2 part. First part is present the waveform of voltage and current, and the second part is about the harmonic order and percentage of Total Harmonic Distortion. The results that gather are analyzed.